(untitled) (Research, Society and Development, 2023)
Oral health care is an integral component of interprofessional collaborative care for children and adolescents diagnosed with cancer. The current literature emphasizes that dental interventions before, during and after cancer treatment improve the quality of life and the integral restoration of health in these patients. The objective of this work was to carry out an integrative literature review on the existence of a dental protocol for the prevention and treatment of oral diseases in children undergoing cancer treatment. Articles published without restriction of years and languages and that included any of the terms as keywords: protocol, childhood cancer, oral disease, oral pathology and oral health were included. The databases used were Pubmed and, as gray literature, an open gray search was performed. The evidence presented here suggests that oral health promotion strategies can reduce the incidence, however it is necessary to develop guidelines to contribute and identify early oral diseases in these children. Thus, it is important to draw up a guide with information on prevention and treatments on oral health for hospitals and clinics specializing in the treatment of childhood cancer, as well as the presence of a pediatric dentist to work collaboratively in the team and thus track, guide, prevent and treat oral pathologies.